SOX2 Expression in Cervical Intraepithelial Neoplasia Grade 3 (CIN3) and Superficially Invasive (Stage IA1) Squamous Carcinoma of the Cervix. (November 2016) - Stewart, Colin J.R.; Crook, Maxine
Abstract : The transcription factor SOX2 plays an important role in tissue development and differentiation. In the neoplastic context, SOX2 has been shown to potentiate tumor invasion, and increased SOX2 immunoreactivity has been demonstrated in a variety of epithelial and nonepithelial malignancies often correlating with adverse prognosis. There are limited data on SOX2 expression in cervical squamous neoplasia and in particular, no studies have compared staining in cervical intraepithelial neoplasia (CIN)3 and in superficially invasive (Stage IA1) squamous cell carcinomas (SCC). We examined SOX2 expression in 12 cervical biopsies showing CIN3 only and 30 specimens with an initial diagnosis of Stage IA1 SCC; 7 of the latter samples did not demonstrate residual invasive foci in the study slides but all showed CIN3. There was variable staining in CIN3 without stromal invasion but CIN3 adjacent to SCC was more often SOX2 positive with 70% cases showing diffuse staining. CIN within endocervical crypts often showed more extensive SOX2 expression and in some cases staining was restricted to areas of crypt involvement. In contrast to CIN, most SCCs were SOX2 negative and there was often an abrupt loss of expression at the tumor-stromal interface. In summary, CIN3 usually showed increased SOX2 expression compared with normal epithelium, particularly in areas of endocervical crypt involvement and adjacent to superficially invasive SCC. However, most invasive tumor cells were unstained suggesting downregulation of SOX2 during the initial stages of the invasive process. Progression of cervical squamous neoplasia may involve cyclical alterations in SOX2 activity.